Conductive polymer sheath material and preparation method thereof

By adding branched conductive polymer polymers and nano nickel fibers to polyvinyl chloride, combined with plasticizers and antioxidants, the shortcomings of existing conductive polymer sheath materials in terms of mechanical properties, processing difficulty and environmental humidity sensitivity are solved, and the high conductivity, high temperature resistance and mechanical properties of the materials are significantly improved.

CN119775686AInactive Publication Date: 2025-04-08JINLONGYING ELECTRICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510280079.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing conductive polymer sheath materials have shortcomings in mechanical properties, processing difficulty and environmental humidity sensitivity, and the compatibility of nanomaterials is limited, which affects the overall performance of the material.

Method used

Based on polyvinyl chloride, branched conductive polymer and nano nickel fibers are added, and plasticizers and antioxidants are combined to form conductive polymer sheath material. Breeding conductive polymers and nano-nickel fibers are prepared by Wilsmeier-Hacker reaction and electrospinning technology to build an efficient conductive network.

Benefits of technology

It significantly improves the conductive properties, high temperature resistance and mechanical properties of the material, ensures the long-term stability and reliability of the material, and reduces the requirements for processing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775686A_ABST
    Figure CN119775686A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive materials, and discloses a conductive polymer sheath material and a preparation method thereof. The conductive polymer material is based on polyvinyl chloride, and is added with branched conductive polymers and nano-nickel fibers. The nano-nickel fibers have good electrical conductivity, and the conjugated structure of the branched conductive polymers can promote electron delocalization and increase electron mobility. The conductive polymer is composited with metal fibers, and the conjugated system of the polymer can serve as a bridge for electron transmission, interconnecting and complementing the electron transmission channels of the metal fibers, expanding the transmission range of electrons in the material, and improving the overall electrical conductivity of the material. The conductive polymer sheath material prepared by the method has good electrical conductivity, high temperature resistance and mechanical properties, and is widely used in cable protection, anti-static of electronic equipment, and power or signal transmission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive materials, and in particular relates to a conductive polymer sheath material and a preparation method thereof. Background Art

[0002] Traditional polymer sheath materials, such as polyvinyl chloride and polyethylene, have long dominated the sheath material market due to their low cost, good processability, and strong insulation.

[0003] In the manufacture and use of electronic equipment, the limitations of traditional polymer sheath materials have become increasingly prominent. Insulating polymer sheaths are prone to static electricity accumulation due to friction, etc. Static electricity may break down electronic components, causing equipment failure, seriously affecting product stability and service life. In flammable and explosive environments, static electricity release may also cause fires, explosions and other serious accidents. Therefore, conductive polymer materials came into being.

[0004] Existing conductive sheath materials usually fill carbon black, carbon nanotubes and other nanomaterials in resin or rubber, which have limited compatibility with the matrix, thus affecting the mechanical properties of the matrix, making processing difficult and more sensitive to environmental humidity. A Chinese patent application with publication number CN 102153878 A discloses a method for preparing a conductive polymer sheath material. The invention is to add nano-scale conductive carbon black and conductive carbon fiber to a thermoplastic polymer resin. Nano-scale conductive carbon black easily absorbs moisture and affects electron transmission; the production process of conductive carbon fiber is complicated, and the fibers are difficult to distribute evenly, which will lead to large differences in the performance of the material in different directions, affecting the overall performance and use effect of the material, and requiring high design and processing technology of the material.

[0005] The Chinese patent application with publication number CN 116199936 A discloses a cable sheath conductive composition, a chloroprene rubber sheath material and a preparation method. The invention uses conductive carbon black and carbon nanotubes and adds iodine. Iodine doping can improve the microstructure inside the conductive material and make the carrier migration in the material smoother. However, iodine has a certain corrosiveness. Especially in a humid environment, iodine may react with metal components or other substances in the conductive material, causing the structure and performance of the material to be damaged. In addition, the sublimation characteristics of iodine are a problem in the application of conductive materials. Iodine has a certain tendency to sublimate at room temperature. As time goes by and the ambient temperature changes, iodine may sublimate and escape from the conductive material, resulting in a decrease in doping concentration, thereby gradually reducing the conductive performance of the material and affecting the long-term stability and reliability of the material. Summary of the invention

[0006] The present invention aims to provide a conductive polymer sheath material and a preparation method thereof. The conductive polymer sheath material is based on polyvinyl chloride, and branched conductive polymers and nano-nickel fibers are added to obtain a conductive polymer sheath material with good conductivity, high temperature resistance and mechanical properties.

[0007] To achieve the above object, the present invention provides a conductive polymer sheath material, comprising polyvinyl chloride, a branched conductive polymer, nano nickel fiber, a plasticizer and an antioxidant; wherein the branched conductive polymer has the following structure: , In the structure, n is an integer between 1 and 10; the mass ratio of the polyvinyl chloride, the branched conductive high molecular polymer, the nano nickel fiber, the plasticizer and the antioxidant is 1: (2-3): (0.5-1): (0.1-0.3): (0.1-0.5).

[0008] Preferably, the plasticizer is any one or more of dioctyl phthalate, dibutyl phthalate, dioctyl adipate, and dioctyl sebacate.

[0009] Preferably, the antioxidant is any one or more of dilauryl thiodipropionate, distearyl thiodipropionate, and tri(2, 4-di-tert-butylphenyl)phosphite.

[0010] The present invention also provides a method for preparing a conductive polymer sheath material, comprising: , Step S1, tetraphenylmethane and a first solvent are mixed, phosphorus oxychloride is added under ice bath conditions, and the reaction is performed to obtain a crude product of methane tetraethyl tetrabenzaldehyde, and the crude product of methane tetraethyl tetrabenzaldehyde is poured into ice water, separated, washed for the first time, dried, and concentrated to obtain methane tetraethyl tetrabenzaldehyde; Step S2, methane tetraethyltetrabenzaldehyde, polyaniline and the first solvent are mixed, a catalyst is added, and a crude branched conductive polymer product is obtained by reaction, a precipitant is added, and the product is filtered, washed for a second time, and freeze-dried to obtain a branched conductive polymer; Step S3, dissolving the nickel salt in the second solvent, mixing with polyacrylonitrile and Tween 80, stirring to obtain nano nickel gel, preparing nano nickel fiber precursor by electrostatic spinning, and calcining to obtain nano nickel fiber; Step S4, the branched conductive high molecular polymer is dissolved in the first solvent, mixed with polyvinyl chloride, and nano nickel fibers, a plasticizer and an antioxidant are added, and stirred to obtain a conductive high molecular sheath material.

[0011] Preferably, the first solvent is any one or more of N, N'-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, and carbon tetrachloride; and the second solvent is an ethanol solution with a volume fraction of 75%.

[0012] Preferably, in step S1, the reaction temperature is 80-100° C., and the reaction time is 10-15 h.

[0013] Preferably, in step S1, the mass ratio of tetraphenylmethane, phosphorus oxychloride and solvent is 1:(0.7-1.2):(4-5).

[0014] Preferably, in step S1, the washing method is alkali washing first and then water washing, the alkali washing solution is any one or more of saturated sodium bicarbonate and sodium hydroxide, and the water washing solution is deionized water.

[0015] Preferably, in step S1, the desiccant used for drying is any one or more of anhydrous magnesium sulfate, anhydrous sodium sulfate, anhydrous sodium carbonate, and anhydrous magnesium carbonate.

[0016] Preferably, in step S1, the concentration temperature is 70-80°C.

[0017] Preferably, in step S2, the catalyst is a Lewis acid, such as any one or more of sulfuric acid, zinc chloride, and aluminum chloride.

[0018] Preferably, in step S2, the reaction temperature is 80-120° C., and the reaction time is 12-18 h.

[0019] Preferably, in step S2, the precipitant is any one or more of petroleum ether, ethyl acetate, n-hexane, and dichloromethane.

[0020] Preferably, in step S2, the washing solution is deionized water.

[0021] Preferably, in step S2, the freeze-drying temperature is -20 to -80°C, and the freeze-drying time is 4 to 6 hours.

[0022] Preferably, in step S2, the mass ratio of the polyaniline, methane tetraethyl tetrabenzaldehyde, the first solvent and the catalyst is 1: (6-12): (10-15): (0.35-1.3).

[0023] Preferably, in step S3, the nickel salt is any one or more of nickel nitrate, nickel sulfate, nickel chloride, and nickel sulfite.

[0024] Preferably, in step S3, the stirring temperature is 30-60°C.

[0025] Preferably, in step S3, the calcination temperature is 500-600°C and the calcination time is 2-3 h. Preferably, in step S3, the mass ratio of nickel salt, polyacrylonitrile, Tween 80 and the second solvent is 1:(1.1-1.5):(1-1.2):(4-5).

[0026] Preferably, in step S3, the electrospinning voltage is 15-20 kV, the temperature is 25-35° C., and the time is 2-4 h.

[0027] Preferably, in step S4, the stirring temperature is 30-45° C., and the stirring time is 2-3 h.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention uses tetraphenylmethane as a starting material, obtains methane tetraethyl tetrabenzaldehyde through the Vilsmayer-Hake reaction, and then reacts with polyaniline to obtain a branched conductive high molecular polymer. Polyaniline has a higher electrical conductivity, and tetraphenylmethane can provide a large steric hindrance, effectively prevent excessive aggregation and entanglement between molecular chains, form a regular molecular arrangement, improve the crystallization performance of the polymer, thereby improving the mechanical properties, solubility and processing properties of the material. Introducing it into the polyaniline system can improve the arrangement and stacking mode of the molecular chains, further improve the mobility of carriers, so that the prepared conductive polymer has a higher electrical conductivity. In addition, the rigid structure of tetraphenylmethane helps to improve the mechanical properties and thermal stability of the conductive polymer. In the heating and stretching process, this rigid structure can limit the thermal motion of the molecular chains, reduce the possibility of changes in the interaction between the molecular chains, so that the conductive polymer can maintain a relatively stable structure and performance at a higher temperature.

[0029] The present invention uses nano nickel fibers and branched conductive high molecular polymers to synergistically improve the conductive properties of the material. The nickel nano fibers and branched conductive high molecular polymers can construct and optimize the conductive network, providing a very low resistance channel for the transmission of carriers. In comparison, although the conductive polymer alone also has a certain conductivity, the carrier transmission efficiency between its molecular chains is relatively low. The conductive network greatly improves the transmission speed and efficiency of the carriers inside the material, thereby significantly improving the conductive properties of the material and ensuring the long-term stability of the conductive properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flow chart for preparing a conductive polymer sheath material. DETAILED DESCRIPTION

[0031] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.

[0032] The main compounds used in the examples and comparative examples are all commercially available products without any further purification.

[0033] Example 1 like Figure 1 As shown, a method for preparing a conductive polymer sheath material comprises the following steps: Step S1, taking 10 g of tetraphenylmethane, dissolving it in 40 g of N, N'-dimethylformamide, adding 7 g of phosphorus oxychloride under ice bath conditions, reacting at 80°C for 10 h to obtain a crude product of methane tetraethyl tetrabenzaldehyde; pouring all the crude product of methane tetraethyl tetrabenzaldehyde into ice water, stirring evenly, standing for stratification, separating the organic phase and the aqueous phase, adding a saturated sodium bicarbonate solution to the organic phase, shaking, standing for stratification, collecting the organic phase, adding anhydrous magnesium sulfate to remove moisture, and concentrating at 70°C to obtain methane tetraethyl tetrabenzaldehyde.

[0034] Step S2, weighing 60 g of methane tetraethyltetrabenzaldehyde and 10 g of polyaniline, dissolving them in 100 g of N, N'-dimethylformamide, adding 3.5 g of zinc chloride, reacting at 80°C for 18 h, and obtaining a crude branched conductive polymer; adding petroleum ether to the crude branched conductive polymer, stirring evenly, standing to wait for precipitation, collecting the solid after filtering, washing with deionized water, and freeze-drying at -20°C for 6 h to obtain a branched conductive polymer.

[0035] Step S3, weighing 10 g of nickel nitrate, 11 g of polyacrylonitrile and 10 g of Tween 80, dissolving them in 30 g of ethanol solution, stirring at 30°C for 9 h to obtain nano-nickel gel, spinning the nano-nickel gel in a 15 kV electrostatic field at 25°C for 4 h to prepare a nano-nickel fiber precursor, and calcining at 500°C for 3 h to obtain nano-nickel fibers.

[0036] Step S4, weigh 10 g of branched conductive polymer, dissolve it in 30 g of N, N'-dimethylformamide, add 40 g of polyvinyl chloride, 5 g of nano nickel fiber, 1 g of plasticizer and 1 g of antioxidant, stir at 30°C for 3 h to obtain a conductive polymer sheath material.

[0037] Example 2 like Figure 1 As shown, a method for preparing a conductive polymer sheath material comprises the following steps: Step S1, weighing 10 g of tetraphenylmethane, dissolving it in 45 g of N, N'-dimethylformamide, adding 10 g of phosphorus oxychloride under ice bath conditions, reacting at 90°C for 15 h to obtain a crude product of methane tetraethyl tetrabenzaldehyde; pouring all the crude product of methane tetraethyl tetrabenzaldehyde into ice water, stirring evenly, standing for stratification, separating the organic phase and the aqueous phase, adding a saturated sodium bicarbonate solution to the organic phase, shaking, standing for stratification, collecting the organic phase, adding anhydrous magnesium sulfate to remove moisture, and concentrating at 70°C to obtain methane tetraethyl tetrabenzaldehyde.

[0038] Step S2, weighing 100 g of methane tetraethyltetrabenzaldehyde and 10 g of polyaniline, dissolving them in 120 g of N, N'-dimethylformamide, adding 8 g of zinc chloride, and reacting at 100°C for 14 h to obtain a crude branched conductive polymer product; adding petroleum ether to the crude branched conductive polymer product, stirring evenly, standing to wait for precipitation, collecting the solid after filtering, washing with deionized water, and freeze-drying at -40°C for 5 h to obtain a branched conductive polymer.

[0039] Step S3, weighing 10 g of nickel nitrate, 13 g of polyacrylonitrile and 11 g of Tween 80, dissolving them in 30 g of ethanol solution, stirring at 45°C for 8 h to obtain nano-nickel gel, spinning the nano-nickel gel in a 20 kV electrostatic field at 30°C for 3 h to prepare a nano-nickel fiber precursor, and calcining at 550°C for 3 h to obtain nano-nickel fibers.

[0040] Step S4, weigh 10 g of branched conductive polymer, dissolve it in 30 g of N, N'-dimethylformamide, add 40 g of polyvinyl chloride, 8 g of nano-nickel fiber, 2 g of plasticizer and 3 g of antioxidant, stir at 40°C for 3 h to obtain a conductive polymer sheath material.

[0041] Example 3 like Figure 1 As shown, a method for preparing a conductive polymer sheath material comprises the following steps: Step S1, weighing 10 g of tetraphenylmethane, dissolving it in 50 g of N, N'-dimethylformamide, adding 12 g of phosphorus oxychloride under ice bath conditions, reacting at 100°C for 10 h to obtain a crude product of methane tetraethyl tetrabenzaldehyde; pouring all the crude product of methane tetraethyl tetrabenzaldehyde into ice water, stirring evenly, standing to separate, separating the organic phase and the aqueous phase, adding a saturated sodium bicarbonate solution to the organic phase, shaking, standing to separate, collecting the organic phase, adding anhydrous magnesium sulfate to remove moisture, and concentrating at 70°C to obtain methane tetraethyl tetrabenzaldehyde.

[0042] Step S2, weighing 120 g of methane tetraethyltetrabenzaldehyde and 10 g of polyaniline, dissolving them in 150 g of N, N'-dimethylformamide, adding 13 g of zinc chloride, reacting at 120°C for 12 h to obtain a crude branched conductive polymer product; adding petroleum ether to the crude branched conductive polymer product, stirring evenly, standing to wait for precipitation, collecting the solid after filtering, washing with deionized water, and freeze-drying at -60°C for 4 h to obtain a branched conductive polymer product.

[0043] Step S3, weighing 10 g of nickel nitrate, 15 g of polyacrylonitrile and 12 g of Tween 80, dissolving them in 30 g of ethanol solution, stirring at 60°C for 6 h to obtain nano-nickel gel, spinning the nano-nickel gel in a 20 kV electrostatic field at 35°C for 2 h to prepare a nano-nickel fiber precursor, and calcining at 600°C for 2 h to obtain nano-nickel fibers.

[0044] Step S4, weigh 10 g of branched conductive polymer, dissolve it in 30 g of N, N'-dimethylformamide, add 40 g of polyvinyl chloride, 10 g of nano-nickel fiber, 3 g of plasticizer and 5 g of antioxidant, stir at 40°C for 2 h to obtain a conductive polymer sheath material.

[0045] Comparative Example 1 A method for preparing a conductive polymer sheath material, which is different from Example 3 in that nickel nitrate is not added in step (3).

[0046] Comparative Example 2 A method for preparing a conductive polymer sheath material, which is different from Example 3 in that no branched conductive polymer is added, but polyaniline conductive polymer is added.

[0047] Performance Test: (1) Conductive properties: According to the method in GB / T 3048, the volume resistivity and surface resistance of the conductive polymer sheath materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested at 20°C.

[0048] (2) Mechanical properties: According to the method in GB / T 2951, the tensile strength, tensile strength and elongation at break of the conductive polymer sheath materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested.

[0049] (3) Anti-aging performance: According to the method in GB / T 2951, the change rate of tensile strength and the change rate of elongation at break of the conductive polymer sheath materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 after heat aging at 100°C for 7 days, the change rate of tensile strength and the change rate of elongation at break of paraffin oil after immersion for 24 hours, and the elongation after being placed at -40°C for 24 hours were tested.

[0050] Table 1 Conductive performance parameters of sheath materials

[0051] The lower the volume resistivity, the smaller the internal resistance of the material, and the better the conductivity; the lower the surface resistivity, the smaller the resistance of the material surface, and the better the surface conductivity. According to the data in Table 1, the conductive polymer sheath materials prepared in Examples 1 to 3 have lower volume resistivity and surface resistance, and experiments have shown that the materials prepared in Examples 1 to 3 have good conductivity. The materials prepared in Comparative Examples 1 and 2 have higher volume resistivity and surface resistance, wherein no nickel salt is added in Comparative Example 1, and no metal fiber forms a conductive network with the branched conductive polymer, and the conductive performance is poor, while the addition of polyaniline conductive polymer in Comparative Example 2 has poor synergistic effect with metal fiber, because there is a lack of strong chemical bonding or effective physical interaction between polyaniline and metal fiber, such as hydrogen bonding, π-π stacking, etc. When subjected to external force, polyaniline and metal fiber are prone to relative sliding or separation, and cannot effectively transfer stress, thereby reducing the effect of synergistic enhancement. In addition, the surface energy of polyaniline is relatively low, and it is difficult to disperse evenly during mixing, and agglomeration is prone to occur, thereby affecting the synergistic effect. The branched polymers added in Examples 1 to 3 are Schiff bases, which contain functional groups such as imine groups in the Schiff base molecules. The nitrogen atoms in these functional groups have lone pairs of electrons and can form coordination bonds with the metal atoms on the surface of the metal fibers. Through the connection of the coordination bonds, a strong chemical bonding force is formed between the Schiff base and the metal fibers, so that they can effectively transfer stress in the composite material and jointly bear external loads, thereby significantly improving the mechanical properties of the composite material and showing a good synergistic reinforcement effect.

[0052] Table 2 Mechanical properties of sheath materials

[0053] According to the data in Table 2, the tensile strength, tensile strength and elongation at break of the conductive polymer sheath material prepared in Examples 1 to 3 are higher than those in Comparative Examples 1 and 2, showing good mechanical properties. No nickel salt is added to the material prepared in Comparative Example 1, and the mechanical properties are slightly lower than those in Examples 1 to 3. This is because the metal itself has a higher strength and modulus. When it is compounded with a polymer material to form a metal polymer composite fiber, the metal part can provide excellent mechanical support for the fiber. In contrast, although the polymer fiber also has a certain strength and modulus, it is usually difficult to reach the level of the metal polymer composite fiber. In the material prepared in Comparative Example 2, a branched conductive polymer is not used, but polyaniline is used as a conductive polymer. The highly branched molecular structure of the branched conductive polymer makes the interaction between the molecular chains more complex and intense. Compared with the relatively linear molecular structure of polyaniline, the structure of the branched conductive polymer can increase the contact points and entanglement between the molecular chains. When the material is subjected to external force, these increased contact points and entanglements can more effectively transmit stress, avoid stress concentration in a local area, and cause the molecular chain to break or slip, thereby significantly improving the mechanical properties of the material.

[0054] Table 3 Anti-aging performance parameters of sheath materials

[0055] According to the data in Table 3, the change rate of tensile strength of the conductive polymer sheath materials prepared in Examples 1 to 3 at 100°C is less than 20%, and the elongation at break is less than 30%, which proves that the materials can maintain good mechanical properties at high temperatures, while the change rates of tensile strength and elongation at break of the materials prepared in Comparative Examples 1 and 2 at 100°C are both greater than 30%, which proves that the materials are aged after 7 days at high temperature.

[0056] After the materials prepared in Examples 1 to 3 were immersed in paraffin oil for 24 hours, the change rate of tensile strength was less than 15%, and the change rate of elongation at break was less than 15%, showing good chemical corrosion resistance. After the materials prepared in Comparative Examples 1 and 2 were immersed in paraffin oil for 24 hours, the change rate of tensile strength and elongation at break were both greater than 20%, and the change rate of tensile strength of the material prepared in Comparative Example 2 was more than 30% after being immersed in paraffin oil for 24 hours. The experimental results show that the materials prepared in Comparative Examples 1 and 2 have aging phenomena in paraffin oil, and the aging of Comparative Example 2 is relatively serious. After being placed in a low temperature environment of -40℃ for 24 hours, the elongation of the conductive polymer sheath materials prepared in Examples 1 to 3 is all above 50%, with good low temperature resistance; Comparative Example 1 is 40.2%, with low temperature resistance, but it is worse than Examples 1 to 3, and the elongation of Comparative Example 2 under the same environment is only 21.5%, which is significantly different from Examples 1 to 3. Experiments have shown that the sheath material prepared by the methods of Examples 1 to 3 has good high temperature resistance, low temperature resistance and chemical corrosion resistance, and can play a role in a variety of scenarios to reduce risks.

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A conductive polymer sheath material, characterized in that: The material includes polyvinyl chloride, branched conductive high molecular polymer, nano nickel fiber, plasticizer and antioxidant; the branched conductive high molecular polymer has the following structure: , In the structure, n is an integer between 1 and 10; the mass ratio of the polyvinyl chloride, the branched conductive high molecular polymer, the nano nickel fiber, the plasticizer and the antioxidant is 1: (2-3): (0.5-1): (0.1-0.3): (0.1-0.5).

2. A conductive polymer sheath material according to claim 1, characterized in that: The plasticizer is any one or more of dioctyl phthalate, dibutyl phthalate, dioctyl adipate, and dioctyl sebacate; the antioxidant is any one or more of dilauryl thiodipropionate, distearyl thiodipropionate, and tris(2, 4-di-tert-butylphenyl)phosphite.

3. The method for preparing a conductive polymer sheath material according to claim 1 or 2, characterized in that: include: Step S1, tetraphenylmethane and a first solvent are mixed, phosphorus oxychloride is added under ice bath conditions, and the reaction is performed to obtain a crude product of methane tetraethyl tetrabenzaldehyde, and the crude product is poured into ice water, separated, washed for the first time, dried, and concentrated to obtain methane tetraethyl tetrabenzaldehyde; Step S2, methane tetraethyltetrabenzaldehyde, polyaniline and the first solvent are mixed, a catalyst is added, and a crude branched conductive polymer product is obtained by reaction, a precipitant is added, and the product is filtered, washed for a second time, and freeze-dried to obtain a branched conductive polymer; Step S3, dissolving the nickel salt in the second solvent, mixing with polyacrylonitrile and Tween 80, stirring to obtain nano nickel gel, preparing nano nickel fiber precursor by electrostatic spinning, and calcining to obtain nano nickel fiber; Step S4, the branched conductive high molecular polymer is dissolved in the first solvent, mixed with polyvinyl chloride, and nano nickel fibers, a plasticizer and an antioxidant are added, and stirred to obtain a conductive high molecular sheath material.

4. The method for preparing a conductive polymer sheath material according to claim 3, characterized in that: The first solvent is any one or more of N, N'-dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, and carbon tetrachloride; and the second solvent is an ethanol solution with a volume fraction of 75%.

5. The method for preparing a conductive polymer sheath material according to claim 3, characterized in that: In the step S1, the reaction temperature is 80-100°C, the reaction time is 10-15 h; the mass ratio of tetraphenylmethane, phosphorus oxychloride and solvent is 1:(0.7-1.2):(4-5); and the concentration temperature is 70-80°C.

6. The method for preparing a conductive polymer sheath material according to claim 3, characterized in that: In the step S1, the first washing method is alkali washing first and then water washing, the alkali washing solution is any one or more of saturated sodium bicarbonate and sodium hydroxide, and the water washing solution is deionized water; the desiccant used for drying is any one or more of anhydrous magnesium sulfate, anhydrous sodium sulfate, anhydrous sodium carbonate, and anhydrous magnesium carbonate.

7. The method for preparing a conductive polymer sheath material according to claim 3, characterized in that: In the step S2, the reaction temperature is 80-120°C, and the reaction time is 12-18 h; the freeze-drying temperature is -20--80°C, and the freeze-drying time is 4-6 h; the mass ratio of polyaniline, methanetetraethyltetrabenzaldehyde, the first solvent and the catalyst is 1: (6-12): (10-15): (0.35-1.3).

8. The method for preparing a conductive polymer sheath material according to claim 3, characterized in that: In step S2, the catalyst is a Lewis acid, such as any one or more of sulfuric acid, zinc chloride, and aluminum chloride; the precipitant is any one or more of petroleum ether, ethyl acetate, n-hexane, and dichloromethane; and the second washing solution is deionized water.

9. The method for preparing a conductive polymer sheath material according to claim 3, characterized in that: In the step S3, the stirring temperature is 30-60°C, and the stirring time is 6-9 h; the calcination temperature is 500-600°C, and the calcination time is 2-3 h; the mass ratio of the nickel salt, polyacrylonitrile and Tween 80 is 1:(1.1-1.5):(1-1.2); the electrospinning voltage is 15-20 kV, the temperature is 25-35°C, and the time is 2-4 h; the nickel salt is any one or more of nickel nitrate, nickel sulfate, nickel chloride and nickel sulfite.

10. The method for preparing a conductive polymer sheath material according to claim 3, characterized in that: In step S4, the stirring temperature is 30-45° C., and the stirring time is 2-3 h.

Citation Information

Patent Citations

  • Preparation method for conductive polymer sheathing material

    CN102153878A

  • Cable sheath conductive composition, chloroprene rubber sheath material and preparation method

    CN116199936A